The Effect Of Financial Literacy and Financial Inclusion On The Intensity Of E-wallet Usage Among Cusstomers at Manakala Coffee Shop Medan - Rahmadani, Adinda Tantri; Hernawaty, Hernawaty; Aulia, Aulia (Journal of Management, Economic, and Accounting, 2026)
The development of financial technology has encouraged the use of e-wallets as a digital payment method, including in culinary businesses such as coffe shops. Although the adoption of e-wallets in Indonesia continues to increase, their intensity of use at the consumer level is not yet optimal and is influenced by behavioral and structural factors. This study aims to analyze the effect of financial literacy and financial inclusion on the intensity of e-wallet usage among consumers at Coffe shop Manakala Medan. This study uses a quantitative approach with a causal associative design. Data were collected through a Likert scale questionnaire distributed to 77 e-wallet users using purposive and convenience sampling techniques. Data analysis was performed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis, which included t-tests, F-tests, and the coefficient of determination (R²). The results of the study indicate that financial literacy has a positive and significant effect on the intensity of e-wallet usage. Financial inclusion also has a positive and significant effect and has a more dominant influence than financial literacy. Simultaneously, both variables have a significant effect on the intensity of e-wallet usage. These findings confirm that the intensity of e-wallet usage is not only determined by the availability of technology, but also by the level of consumer understanding and ease of access to digital financial services. This study provides empirical evidence by emphasizing the importance of financial literacy and financial inclusion in promoting the sustainable use of e-wallets in the culinary business.